Біологічні аспекти сортового обрізування персика в зрошуваних умовах Південного Степу України. - Алексєєва, Ольга Миколаївна; Alekseeva, Olha; Юдицька, Ірина Валеріївна; Yudytska, Iryna (Одеса : Видавничий дім «Гельветика», 2023)
UKR: Висвітлено результати дослідження основних аспектів формування врожайності персика залежно від впливу сортових особливостей та погодних факторів навколишнього середовища досліджуваних років для коригування основної нормуючої обрізки насаджень культури. Головна роль у формуванні врожаю якісних плодів персика належить силь- ним річним пагонам та передчасним. Найважливішим показником потенційної продук- тивності даної культури є закладання та диференціація генеративних бруньок на цих приростах. В роботі визначено більш адаптовані сорти персика до ґрунтово-кліматич- них умов Степової зони України. По ступені диференціації генеративних бруньок влітку 2020 року під врожай 2021 року сформовано 4 групи: з закладкою на погонному метрі сильно змішаного пагона від 0 до 10 генеративних бруньок – Кардинал: 10–20 генератив- них бруньок – Клоун і Вавіловський; 20–30 генеративних бруньок – Посол Миру; 30–40 генеративних бруньок на погонному метрі сильного змішаного річного приросту – Кан- дидатський, Освіжаючий, Сатурн і Єрлі Редхейвен. Сприятливі умови 2021 року під час диференціації генеративних бруньок ступінь їх закладки по сортах змінилася: 50–60 гене- ративних бруньок на один погонний метр – Клоун, Кандидатський, Сатурн і Кардинал; 61–70 шт./пог.м – Посол Миру; 71–80 шт./пог.м – Освіжаючий і Вавіловський; 81–90 – Ерлі Редхейвен. Отримані результати необхідно обов’язково враховувати при нормуванні врожаю під час обрізки. Визначено, що сорти Освіжаючий, Ерлі Женева і подібних їм по ступеню закладки генеративних бруньок (при 85–100% збереженності взимку), рекомен- дується обрізати з видаленням від 60 до 70% однорічного приросту; сортів Посол миру, Сатурн, Вавіловський і Кандидатський максимально до 50%, і у сортів Кардинал і Клоун при обрізуванні видаляти від 35 до 40% однорічного приросту./////////////// ENG : The results of the study of the main aspects of the formation of peach yield depending on the influence of varietal characteristics and weather factors of the environment of the studied years for the adjustment of the main normative pruning of crop plantations are highlighted. The main role in the formation of a harvest of high-quality peach fruits belongs to strong annual shoots and premature ones. The most important indicator of the potential productivity of this culture is the establishment and differentiation of generative buds on these growths. The work identifies peach varieties that are more adapted to the soil and climatic conditions of the Steppe zone of Ukraine. According to the degree of differentiation of generative buds in the summer of 2020 for the harvest of 2021, 4 groups were formed: with a tab on a running meter of a strongly mixed shoot from 0 to 10 generative buds – Cardinal: 10–20 generative buds – Clown and Vavilovsky; 20–30 generative buds – Ambassador of Peace; 30–40 generative buds per linear meter of strong mixed annual growth – Candidate, Refreshing, Saturn and Early Redhaven. Favorable conditions in 2021 during the differentiation of generative buds, the degree of their establishment by varieties has changed: 50–60 generative buds per linear meter – Clown, Candidate, Saturn and Cardinal; 61–70 pcs./p.m. – Ambassador of Peace; 71–80 pcs./unit.m – Refreshing and Vavilovsky; 81–90 – Early Redhaven. The obtained results must be taken into account when rationing the crop during pruning. It was determined that the varieties Osvizhyachyy, Early Geneva and similar to them in terms of the degree of laying of generative buds (with 85–100% preservation in winter) are recommended to be pruned with the removal of 60 to 70% of the annual growth; of the Ambassador of Peace, Saturn, Vavilovsky and Kandidatsky varieties up to 50%, and in the Cardinal and Clown varieties, when pruning, remove from 35 to 40% of the annual growth.
Biological aspects of varietal pruning of peach in irrigated conditions of the Southern Steppe of Ukraine.
Keywords: персик; сорти персика; обрізка персика; погодні умови; структура річного приросту; диференціація генеративних бруньок; peach; varieties; pruning; weather conditions; structure of annual growth; differentiation of generative buds